2017
DOI: 10.22616/erdev2017.16.n314
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mastitis detection index for cow monitoring and abnormal milk detection in milking robots

Abstract: Abstract. The aim of the study was to evaluate the effectiveness of the Mastitis Detection index (MDi) for detection of cows with a high somatic cell count (SCC) during milking in the milking box of the DeLaval milking robot. The MDi takes conductivity, milking intervals and blood presence into consideration. All these factors and SCC dynamics were analyzed in 20 cows during a three-week period. The MDi was compared between the experimental group (cows with initial MDi 1.4 or more, n = 10) with the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…With a higher MDi threshold, no better SN was detected in our study. This contradicts in part the approach of Lusis et al [ 56 ], which suggested an MDi threshold of ≥2 for abnormal milk detection to keep the SCC of bulk tank milk at a low level. While the higher threshold markedly increased the SP, the SN decreased drastically.…”
Section: Discussionmentioning
confidence: 82%
“…With a higher MDi threshold, no better SN was detected in our study. This contradicts in part the approach of Lusis et al [ 56 ], which suggested an MDi threshold of ≥2 for abnormal milk detection to keep the SCC of bulk tank milk at a low level. While the higher threshold markedly increased the SP, the SN decreased drastically.…”
Section: Discussionmentioning
confidence: 82%
“…The differences in the results might be due to the nature of the different outcomes studied (SCC vs. clinical mastitis defined as veterinary treatment), model choice (nonlinear vs. linear model), difference in milking interval, or available data (one vs. two herds). Furthermore, Lusis et al (2017) found the correlation between SCC and MDi to be poor; however, due to the small sample size and few observations in their study, the authors suggested that individual cows might have affected the results. When MDi and UC were excluded (model 2), variance in conductivity between quarters had the strongest statistical association with CMSCC.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, Lusis et al . (2017) found the correlation between SCC and MDi to be poor; however, due to the small sample size and few observations in their study, the authors suggested that individual cows might have affected the results.…”
Section: Discussionmentioning
confidence: 85%
“…For example, "Afimilk" company explains the methods chrestomatic basics in its website (Anonymous, 2010), and numerous scientific publications explain it in even more detail, with practical aspects (Anonymous, 2020a) or in depth chemical basics (Romero et al, 2016;Muchetti et al, 1993). The benefits of regular conductometric tests in veterianary aspects are discussed in (Lusis et al, 2017). New at our job was the hardware realisation method by means of iNA-170 giving more simple, accurate and effective implementation of measurement physically-chemical principle in comparison with other concurrent electronics, for example, instrumental amplifier in quadrature envelope detector.…”
Section: Results: Measure-system Efficiencymentioning
confidence: 99%